Parental Assistance In Learning From Home Activities To Self-Efficacy In Children Aged 4-6 Years - Delina Kasih; Fitria Budi Utami (Universitas Muhammadiyah Ponorogo, 2022)
This study aimed at analyzing the effect of parental assistance in learning activities from home on the self-efficacy in children aged 4-6 years in RW 03 Rawa Bunga, Jatinegara, East Jakarta. This research used the survey method and Pearson Bivariate Correlation analysis. Samples were taken 55% of the total population, namely 30 parents. The sampling technique used in this research was purposive sampling. The data collection technique used in this research was a questionnaire technique (questionnaire) for the two variables. This study resulted in a regression equation Y= 49.011 + 0.511X with the results of the correlation coefficient test yielding 0.429; and the coefficient of determination 18.4% interpreted the effect of parental assistance in learning activities from home on the self-efficacy in children aged 4-6 had a significant positive effect, the influence of parental assistance had a sufficient correlation on children's self-efficacy and parental assistance has an effect of 18.4% of the self-efficacy in children aged 4-6 years in RW 03 Rawabunga, Jatinegara, East Jakarta.